2021
DOI: 10.3389/fphar.2021.748501
|View full text |Cite
|
Sign up to set email alerts
|

Grey Relational Analysis Combined With Network Pharmacology to Identify Antioxidant Components and Uncover Its Mechanism From Moutan Cortex

Abstract: The present study determines the potential antioxidants in Moutan Cortex (MC) and predicts its targets of anti-oxidative activities. The quantitative analysis and the free radical scavenging assays were conducted to detect the main components in MC and assess its anti-oxidant activities. The grey relational analysis and the network pharmacology approach were employed to predict its key components and targets of anti-oxidant activities. Six main constitutes in MCs were quantified by high performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Our data also showed that LPS increased the amount of ROS and MDA and reduced the activity of SOD antioxidant enzymes. The chemical structure of PF endows it with strong antioxidant properties and PF exerts its antioxidant effect by transferring electrons to form stable molecules from free radicals (Zhang et al, 2021). With continuous in‐depth research on PF, its pharmacological effects are constantly being discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that LPS increased the amount of ROS and MDA and reduced the activity of SOD antioxidant enzymes. The chemical structure of PF endows it with strong antioxidant properties and PF exerts its antioxidant effect by transferring electrons to form stable molecules from free radicals (Zhang et al, 2021). With continuous in‐depth research on PF, its pharmacological effects are constantly being discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The retention of antioxidant activity of PNL and FPNL under external environmental stimulation were then measured daily from the supernatant after UV irradiation. The antioxidant activity of FPNL and PNL was determined by using a DPPH and ABTS radical scavenging assay ( 23 ). 2,2-Diphenyl-1-picrylhydrazyl powder was dissolved in 100 ml methanol to prepare the 0.05 mM DPPH solution for the method.…”
Section: Methodsmentioning
confidence: 99%
“…The ABTS radicals scavenging was reacting ABTS and potassium persulfate ( 23 ). The mixture was incubated in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…( Chen et al, 2020 ), Moutan Cortex (the dried bark of Paeonia suffruticosa Andr.) ( Zhang et al, 2021 ), Paeoniae Radix Rudra (the root of Paeonia lactiflora Pall. or Paeonia veitchii Lynch) ( Tan et al, 2020 ), Linderae Radix [the dried root of Lindera aggregata (Sims) Kos-term.]…”
Section: Introductionmentioning
confidence: 99%